Notes for "Welcoming Remarks" to National U.S./Mexico Sister City Association Board of Directors Meeting - Jane Tolmach::::::
Notes for a speech presented at the National U.S./Mexico Sister City Association Board of Directors Meeting welcoming the members to Oxnard.